Hubungan antara Indeks Masa Tubuh dengan Tekanan Darah dan Golongan Darah di Kelurahan Mersi Kecamatan Purwokerto Timus - Destyana R,; Saryono,; Mursiyam, (Jurusan Keperawatan FIKES UNSOED, 2009)
Multiple nutrition problems is complicated, it is caused by change of life style and diet pattern. Some study stated that eating habits consuming of fast food can increase blood pressure. In addition, some certain food such as lecithin has relation to certain blood type, it cause healthy problems such as obesity. The aim this study is to know the correlation between body mass index with blood pressure and blood type in Sub District of Mersi District of East Purwokerto.The crossectional study used to assess body mass index, blood pressure and blood type in 63 respondents that fulfill in inclusion criteria. Sample research was taken by simple random sampling. The average of respondent have normal body mass index category it is 34 respondents (54%), normal blood pressure category is 35 respondents (55,6%), and blood type respondent is blood type A at 22 respondents (34,9%). The correlation between body mass index with blood pressure have grade Chi Square test 0,001 with p 1,000 more than ? 0,05 and correlation between blood type with body mass index have grade chi square test 18,792 with p 0,001 less than ? 0,05. There was no correlation between body mass index with blood pressure but there was correlation between blood type with body mass index in Sub District of Mersi District of East Purwokerto.